Abrupt increase in phosphorus and potassium fluxes during a masting event in a Bornean tropical forest. Issue 6 (13th August 2018) - Aoyagi, Ryota; Imai, Nobuo; Hidaka, Amane; Samejima, Hiromitsu; Kitayama, Kanehiro
Abstract: Mechanisms by which the productivity of tropical ecosystems is limited by nutrients is a long‐standing question, but little information is available on the nutrient dynamics supporting the masting phenomenon in Southeast Asian evergreen rainforests. In this study we examined the nutrient sink and potential nutrient sources of masting in a Bornean tropical forest. We investigated if nutrient flux in fine litter, tree stems, and soils changed temporally in response to intense flower and fruit production. Fifty‐five litter traps were installed in a 2‐ha plot at the onset of flowering (April 2010), and litter and nutrient fluxes were monitored for more than 4 years (May 2010–December 2014). Wood cores of trunks and coarse roots of abundant species ( Shorea spp.) and soil samples were collected in May 2010, September 2010, and September 2011 (coinciding with peak flowering, peak fruiting, and 1 year after fruiting, respectively). The P and K fluxes in the total litter were significantly greater in the mast year (2010) than non‐mast years, whereas the Mg, N, and Ca fluxes did not vary in relation to masting. In line with the nutrient fluxes, P and K concentrations in coarse roots of flowering individuals of S. multiflora decreased in September 2011. The present results suggest that tropical trees require extraordinary amounts of P and K for masting, and may retranslocate stored nutrients to meet the elevated nutrient demands for masting.